Comparative analysis on the efficiency of the firm and theirs determinants of European transition economics - Moreno, Justo de Jorge; Castillo, Leopoldo Laborda (Journal of Business Economics and Management, 2013)
In this study we evaluate the efficiency of the firms with DEA technique and bootstrapping procedure in eleven transition economics among sixth industrial and service sectors in a cross-section 2005. At the second stage, we study the relationship between corrected efficiency scores and possible explanatory variables. On one hand, our result shows statistically significant differences in efficiency levels across countries and sectors. Likewise, significant levels of inefficiency are identified especially in service sectors (Hotels and Restaurants, Retail and Wholesale and Transport). On the others hand, the results of the analysis in second stage confirmed the existence of a significant relationship between the country that firms operate (country-effect) and firm′s age (learning by doing). The latter relationship between age and efficiency has different behaviors according to the sector concerned, in the form of U shape in the Hotels and Restaurants, inverted U shape in Metal and Machinery and Wood and Furniture and linear in the Retail and Wholesale sector. Contrary perhaps to expectations, the results also allow us to conclude that there is no important statistically significant relationship between the efficiency and variables related to the strategies implemented by firms and the control of the property.